2022
DOI: 10.1111/1756-185x.14444
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with cytomegalovirus infection in antineutrophil cytoplasmic antibody‐associated vasculitis: A narrative review

Abstract: Patients with antineutrophil cytoplasmic antibody‐associated vasculitis (AAV) are vulnerable to opportunistic infections, including cytomegalovirus (CMV) infection. This narrative review aims to identify factors associated with CMV infection in patients with AAV. The literature review was conducted on Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane, PubMed, Scopus, and Web of Science. The start date of the literature search was unrestricted and the end date was February 2022. CMV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…Clinically we estimated the infection risk by initial IgG levels (Table S2), however, a recent study suggested that the minimum of post-treatment IgG levels is important for the risk estimation. 39 The risk of CMV infection has also been reported in patients with AAV, 46,47 and CMV infection is associated with other infections and thromboembolism. 48,49 In our patients, infection affected the composite outcome of ESRD or death in patients as previous literature.…”
Section: Ta B L Ementioning
confidence: 99%
“…Clinically we estimated the infection risk by initial IgG levels (Table S2), however, a recent study suggested that the minimum of post-treatment IgG levels is important for the risk estimation. 39 The risk of CMV infection has also been reported in patients with AAV, 46,47 and CMV infection is associated with other infections and thromboembolism. 48,49 In our patients, infection affected the composite outcome of ESRD or death in patients as previous literature.…”
Section: Ta B L Ementioning
confidence: 99%